Sustained impact of rotavirus vaccine introduction on rotavirus gastroenteritis hospitalizations in children <5 years of age, Ghana, 2009–2016. Issue 47 (12th November 2018) - Enweronu-Laryea, Christabel C.; Armah, George; Sagoe, Kwamena W.; Ansong, Daniel; Addo-Yobo, Emmanuel; Diamenu, Stanley K.; Mwenda, Jason M.; Parashar, Umesh D.; Tate, Jacqueline E.
Abstract: Introduction: Ghana introduced monovalent rotavirus vaccine in April 2012. We sought to determine the long-term impact of routine rotavirus vaccination on rotavirus gastroenteritis hospitalizations in Ghana during the first 4 years following rotavirus vaccine introduction. Methods: Active sentinel surveillance for acute gastroenteritis hospitalizations among children <5 years of age was conducted at two sites from July 2009 through June 2016. Stool specimens were collected from enrolled children and tested by enzyme immunoassay. Changes in the proportion of all-cause gastroenteritis hospitalizations due to rotavirus pre- (July 2009–June 2012) and post-vaccine introduction (July 2012–June 2016) were compared using chi-square test. Results: The proportion of acute gastroenteritis hospitalizations due to rotavirus among children <5 years of age significantly declined by 42% from a pre-vaccine median of 50% (343/684) to a post-vaccine median of 29% (118/396) (p < 0.001). The age distribution of rotavirus hospitalizations shifted toward older ages with 64% (759/1197) of rotavirus hospitalizations occurring in children <12 months of age pre-vaccine introduction to 47% (212/453) occurring in children <12 months of age post-vaccine introduction (p < 0.001). Discussion: The decline in rotavirus hospitalizations following rotavirus vaccine introduction have been sustained over the first 4 years of the vaccination program in Ghana. Continued vaccination against rotavirus will ensure that this burden remains low.